Menakar Urgensi Pemberian Insentif Perpajakan bagi Perempuan di Indonesia - Tambunan, Maria R.U.D.; Arion, Grace (Jurnal Pemerintahan dan Politik, 2025)
The issue of gender equality in Indonesia has begun to penetrate the economic sector because there is a disparity in the wages received by Indonesian women, which are below the global average. Indonesia also experiences relatively high labor force disparities. Women can increase the country's productivity up to IDR 28 trillion, equivalent to 26% of the world's GDP. The government is considering gender equality in decision-making, including in the realm of taxation, one of which is through gender-based taxation. World researchers are also trying to disentangle the justice in taxation with a gender perspective to provide a new perspective in policy formulation for the government. On the other hand, some literature argues the need to apply gender-based taxation incentives in developing countries. This study attempts to unravel the urgency of implementing gender-based taxes in Indonesia and how best practices are from other countries that have implemented gender-based taxation. This study uses qualitative methods with data collection techniques, namely secondary data literature studies. Based on this research, there is an urgent to provide tax incentives to women, especially working married and giving birth woman, as a gender-based taxation embodiment. In addition, it was found that Singapore has implemented a gender-based taxation incentive scheme for women giving birth, and it has been running very well until now.